Rod‐Shaped Active Drug Particles Enable Efficient and Safe Gene Delivery. Issue 11 (5th September 2017) - Xin, Xiaofei; Pei, Xue; Yang, Xin; Lv, Yaqi; Zhang, Li; He, Wei; Yin, Lifang
Abstract: Efficient microRNAs (miRNA) delivery into cells is a promising strategy for disease therapy, but is a major challenge because the available conventional nonviral vectors have significant drawbacks. In particular, after these vectors are entrapped in lysosomes, the escape efficiency of genes from lysosomes into the cytosol is less than 2%. Here, a novel approach for lethal‐7a (let‐7a) replacement therapy using rod‐shaped active pure drug nanoparticles (≈130 nm in length, PNPs) with a dramatically high drug‐loading of ≈300% as vectors is reported. Importantly, unlike other vectors, the developed PNPs/let‐7a complexes (≈178 nm, CNPs) can enter cells and bypass the lysosomal route to localize to the cytosol, achieving efficient intracellular delivery of let‐7a and a 50% reduction in expression of the target protein (KRAS). Also, CNPs prolong the t 1/2 of blood circulation by ≈threefold and increase tumor accumulation by ≈1.5–2‐fold, resulting in significantly improved antitumor efficacies. Additionally, no damage to normal organs is observed following systemic injection of CNPs. In conclusion, rod‐shaped active PNPs enable efficient and safe delivery of miRNA with synergistic treatment for disease. This nanoplatform would also offer a viable strategy for the potent delivery of proteins and peptides in vitro and in vivo. Abstract : An approach for microRNAs (let‐7a) replacement therapy based on rod‐shaped pure drug nanoparticles (PNPs) is reported. PNPs deliver let‐7a to cancer cells bypassing the lysosomal route and enable twofold increase of let‐7a and threefold decrease of target protein in tumor and ≈100% inhibition of tumor‐growth and lung‐metastasis. This work provides a valuable nanoplatform for efficient and safe gene delivery.